Akuntabilitas Dan Transparansi Terhadap Pelaporan Keuangan Dana Sumbangan Masjid (Studi Khasus Masjid Fastabiqul Qairot) - Dewi Tri Darinda; Yunita Dwi Anggraini; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Mosques are often in the public spotlight in terms of openness regarding the finances of mosque donations given by donors. Thus, indirectly the manager of the mosque tries to convey information that can increase accountability and the success of the organization even though this information is not required. The application of accounting is a form of accountability and transparency that can narrow the information gap between mosque managers and the public. The problem that has been happening in the community is the lack of public awareness (jama’ah) about the importance of transparency and accountability in mosque financial management and mosque financial records that only use manual processes and are not supported by information system technology.